Glycosylated Haemoglobin as A Marker of Severity in Patients with Acute Myocardial Infarction - Dr. Kumar Ujjwal; Dr. D. P. Lakra; Dr. M. Khande (International Journal of Pharma and Bio Sciences, 2023)
Hyperglycaemia is an independent risk factor for cardiovascular diseases (CVD). Glycosylated hemoglobin A1c (HbA1c) is a pivotal bio-marker reflecting fasting and postprandial plasma glucose concentration over the preceding 2–3 months. And also, it has been regarded as an important tool in diabetes diagnosis and management. The study evaluated the utility of HBA1c in determining the severity of Acute Myocardial Infarction in Tertiary Care Hospitals. The prospective analytical cross-sectional study was carried out among 169 patients aged 18 years and above admitted with Acute myocardial infarction at a tertiary care center from November 2021 to October 2022. The severity of MI was done using TIMI Score for STEMI/ NSTEMI. The collected data were analyzed with proper statistical methods using MS Excel 2016. Data were summarized in percentages and proportions. P value <0.05 was considered statistically significant. The mean age of the patients was 60.50 ±10.94 years, with the majority of cases being male. (63.91%) There was a strong association between the risk category and HbA1c with statistically significant differences. TIMI risk score had a strong positive correlation with HbA1c. (P<0.0001) The present study concludes a significant correlation between HbA1c levels and the severity of Acute Myocardial Infarction.